Analisis Semiotika Komunikasi Visual Brand Lafiye dalam Membangun Brand Image melalui Website - Afilika, Ganis Filma; Batubara, Abdul Karim (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study analyzes the visual communication strategy and brand image formation through multimodal elements on the Lafiye website. Using a qualitative approach with Roland Barthes' semiotic analysis, this research examines brand identity representations across the homepage, product pages, and the "Anniversary Backstage" campaign based on Kevin Lane Keller’s Brand Association dimensions. The findings reveal that Lafiye establishes a unique, strong, and favorable brand image by deconstructing the perception of modest fashion into an authoritative figure. This is visually represented through piercing eye contact, bold makeup, and specialized photography techniques emphasizing material drapability. In the anniversary campaign, the use of horizontal shawl accents and shimmering details symbolically communicates brand stability and a decade of success. The integration of philosophical narratives with minimalist aesthetics successfully creates an authentic "Glamorous Minimalism" brand association. The study concludes that the Lafiye website functions effectively as a visual communication instrument to shape consumer perceptions of empowerment and a modern lifestyle. This multimodal synergy reinforces the brand's positioning within the competitive modest wear industry.